Students’ experiences in teaching and learning Islamic education using philosophical inquiry method - Wan Yusoff, Wan Mazwati; Preece, Abdul Shakour Duncan; Hamzah, Lina Mursyidah (Universitas Ahmad Dahlan (UAD) in collaboration with Institute of Advanced Engineering and Science (IAES), 2018)
Studies have shown that traditional chalk and talk teaching methods are common among teachers of Islamic Education. Such teacher-centered pedagogy fails to promote active learning or interaction between the teacher and students; and between students and students. The result is a lack of interest in learning because students are not stimulated or engaged by interesting classroom activity or pedagogy. Numerous studies conducted by a host of countries have proven that Philosophical Inquiry Method (PIM) is effective in promoting discussion and getting students to be actively involved in learning, as they discover new meanings. Having said this, little is known about the impact PIM on Malaysian Islamic Education students' engagement. Therefore, an exploratory case study was conducted to gauge students’ views and experiences of PIM to teach aqidah (creed). The study involved students aged 13 – 14 years old who were in Form 2 at an Islamic secondary school in Selangor, focusing particularly on the Islamic Education subject of aqidah. After completing six philosophical inquiry sessions, four students were interviewed to gauge their responses to the programme. The results of the study showed that students found the lessons easier to understand, as they explored beyond the content of the textbook and they enjoyed this new pedagogy. In the light of this, it can be said that PIM gave students a positive learning experience for the subject of aqidah.